Nitrate control and quality in hydroponic lettuce by using cow dung extract and nutrient solution - Abu Raihan; Md. Jahedur Rahman; Chand Sultana Chandni; Sabina Yasmin; Md. Shahajahan Ali (Journal of Applied Botany and Food Quality, 2023)
Hydroponically grown lettuce poses a high nitrate risk, raising concern about its quality. Therefore, this work was employed to determine the accumulation of nitrate in lettuce leaf and the phytochemical properties of hydroponic lettuce. Treatments considered as four different levels of aerated cow dung extracts (CD), viz., CD1 = 50 g.L-1, CD2 =100 g.L-1, CD3 =150 g.L-1 and CD4 =200 g.L-1 and four strengths of standard nutrient solution (S), viz, S1 = 30% of standard nutrient solution, S2 = 40% of standard nutrient solution, S3 = 50% of standard nutrient solution and S4 = 60% of standard nutrient solution. The experiment was carried out in a deep flow technique in semigreenhouse. In the case of cow dung extract, the highest total fresh weight (112.05 g/plant) was recorded from CD3 while the lowest in CD1 and for nutrient solution, the highest fresh weight (116.0 g/plant) was recorded from S4 while the lowest in S1. In the event of, nitrate and ascorbic acid content were statistically higher in CD4 followed by CD3 and the lowest in CD1. In case of nutrient solution, the nitrate content was highest in S4 and the lowest in S1. The highest fresh weight and almost all the parameters were found to be the best in CD3S4 and the lowest in CD1S1. Therefore, the analysis showed that CD3S4 would be the most preferable treatment combination for producing quality lettuce with the lower content of nitrate.